Karyotype variation in lesser short-nosed fruit bat Cynopterus brachyotis (Müller 1838) from Special Region Yogyakarta, Indonesia - Husni Mubarok; Niken Satuti Nur Handayani; Ibnu Maryanto; Tuty Arisuryanti (Society for Indonesian Biodiversity, 2021)
Abstract. Mubarok H, Handayani NSN, Maryanto I, Arisuryanti T. 2021. Karyotype variation in lesser short-nosed fruit bat Cynopterus brachyotis (Müller 1838) from Special Region Yogyakarta, Indonesia. Biodiversitas 22: 2560-2568. Lesser short-nosed fruit bat Cynopterus brachyotis is a widespread fruit bat in different habitats. This species is suspected to have chromosome morphology variation, since karyotype data in Indochinese Peninsula, Borneo, West Java, and the Philippines has been revealed. Karyotype data can provide basic information on taxonomic relationships, evolutionary origins, and genetic aberrations. This study aimed to analyze karyotype variation in C. brachyotis from different habitats in a special region of Yogyakarta, Indonesia. Total 14 sample bats were mist-nets trapped, including six individuals from an urban area, three individuals from natural forest, and five individuals from mangrove forest. Chromosome preparations were conducted using the splash method with bone marrow, including treatment of colchicine 0.005%, 0.075M KCl solution, Carnoy solution, and Giemsa staining. Chromosome was analyzed and classified using ImageJ Levan Plugin software. The result showed C. brachyotis from different habitats in this study indicated karyotype variation and have different karyotype from West Java samples. Males C. brachyotis from mangrove forest have a karyotype formula of 2n=34, FN=61, 16m+8sm+2st+6t, X=st, and Y=t, while female C. brachyotis from the urban area have karyotype formula of 2n=34, FN=62, 16m+4sm +6st+6st, and X=st.